2023
DOI: 10.3389/fendo.2023.1087845
|View full text |Cite
|
Sign up to set email alerts
|

Expression of placental glycans and its role in regulating peripheral blood NK cells during preeclampsia: a perspective

Abstract: Preeclampsia is a pregnancy-related multisystem disorder characterized by altered trophoblast invasion, oxidative stress, exacerbation of systemic inflammatory response, and endothelial damage. The pathogenesis includes hypertension and mild-to-severe microangiopathy in the kidney, liver, placenta, and brain. The main mechanisms involved in its pathogenesis have been proposed to limit trophoblast invasion and increase the release of extracellular vesicles from the syncytiotrophoblast into the maternal circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 256 publications
(285 reference statements)
0
1
0
Order By: Relevance
“…5d, e and Supplementary Fig. 11b), why may implicate reproductive complications, including preeclampsia, intrauterine growth restriction, and an increased risk of miscarriage (49)(50)(51). Conversely, we observed a downregulation of pathways involved in lipid metabolism, phosphatidylinositol signaling, inositol phosphate metabolism, and ABC transporters (Fig.…”
Section: Mps Exposure Led To Tissue-specific Transcriptomic Aberratio...mentioning
confidence: 68%
“…5d, e and Supplementary Fig. 11b), why may implicate reproductive complications, including preeclampsia, intrauterine growth restriction, and an increased risk of miscarriage (49)(50)(51). Conversely, we observed a downregulation of pathways involved in lipid metabolism, phosphatidylinositol signaling, inositol phosphate metabolism, and ABC transporters (Fig.…”
Section: Mps Exposure Led To Tissue-specific Transcriptomic Aberratio...mentioning
confidence: 68%
“…Hypoxia may be one of these factors, since it (i) results from placental pathology, which is caused by morphologic or occlusivestenotic malformations of the vessels of fetoplacental complex, and is a characteristic sign of early-onset and late-onset PE; (ii) is both a factor that stimulates the development of sterile systemic inflammation and endothelial dysfunction in response to placental damage [35,36], and a factor destabilizing the eGC [37][38][39], thus leading to hemodynamic disorders; (iii) is one of the key stimulating factors of angiogenesis [40,41], which is impaired in patients with placenta-associated complications of pregnancy, in particular, PE and FGR [42,43]; and (iv) is a regulator of glycan expression in human placental structures [44] (in particular, hypoxia stimulates the expression of fucosylated glycans on the surface of endothelial cells) [45,46]. It should also be noted that, in addition to hypoxia, changes in the expression of glycans, including fucoglycans, activate pro-inflammatory factors [47,48]. Based on the above facts, we suggested that the expression of fucosylated glycans in the eGC of fetal capillaries of the placental terminal villi is connected with maternal and fetoplacental hemodynamic parameters, as well as with the factors reflecting the degree of development of systemic inflammatory response and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%